Experimental study on the strain contribution of horizontal and vertical web reinforced bar of HSSCC deep beams - Mohammadhassani, M.; Jumaat, Mohd Zamin; Jameel, M.; Hakim, S.J.S.; Abdollahi, N. (2012)
Deep beams are structural elements loaded as beams in which a significant amount of the load is transferred to the supports by a compression strut trajectory joining the loads and the reactions. A comparative study is performed to predict the strain contribution of horizontal and vertical web bar located at compression strut trajectory from support points to load points. For investigation in this purpose, three high strength self compacted concrete (HSSCC) rectangular-section deep beams with the length to depth ratio less than three were designed based on American Concrete Institute (ACI) code with variation of tensile bar percentage and casted and loaded in laboratory. The longitudinal, web steel strains and concrete strains were measured for every incremental load. Before of first crack occurrences, the vertical bar strain is more than horizontal bar strain. When first crack happened, strain in vertical and horizontal web bar was same and by load increasing the strain in horizontal increased more than vertical. The strain became more than two times in horizontal bras comparison to strain in vertical bar when tensile bar yielded. At ultimate load the strain contribution of horizontal bar was more than four times in comparison by vertical bars.